2017
DOI: 10.1209/0295-5075/120/25002
|View full text |Cite
|
Sign up to set email alerts
|

Field-emission enhanced breakdown in oxygen microdischarges from direct-current to radio-frequencies

Abstract: This paper reports on experimental studies of the breakdown mechanism in oxygen microdischarges generated in static and time-varying electric fields, up to radio-frequencies. Measurements were performed by using electrodes with round edges separated by a distance ranging between and , with the gas pressure from 7.5 Torr to 700 Torr. It is shown that the breakdown voltage does not obey standard scaling law for gaps of the order of a few microns for both direct current and alternating fields. A high electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Levko and Raja studied the microwave breakdown process in the micro-gap under atmospheric pressure and found that the breakdown voltage of microwave and direct current (DC) micro-discharge under different gap lengths had different trends, when the gap length exceeded a critical value, only the initial seed electrons in the gap can cause microwave micro-discharge [19]. Klas et al studied the breakdown mechanism of oxygen micro-discharge under static, time-varying electric fields and radio frequencies through experiments, and the FE threshold determined by the experimental data is more consistent with the literature [20]. Meng et al evaluated the mechanism of pulse voltage micro-scale gas breakdown and showed that the DC micro-scale gas breakdown theory is also applicable to pulse breakdown, with Townsend avalanche mode transition to FE being driven breakdown [21].…”
Section: Introductionmentioning
confidence: 58%
“…Levko and Raja studied the microwave breakdown process in the micro-gap under atmospheric pressure and found that the breakdown voltage of microwave and direct current (DC) micro-discharge under different gap lengths had different trends, when the gap length exceeded a critical value, only the initial seed electrons in the gap can cause microwave micro-discharge [19]. Klas et al studied the breakdown mechanism of oxygen micro-discharge under static, time-varying electric fields and radio frequencies through experiments, and the FE threshold determined by the experimental data is more consistent with the literature [20]. Meng et al evaluated the mechanism of pulse voltage micro-scale gas breakdown and showed that the DC micro-scale gas breakdown theory is also applicable to pulse breakdown, with Townsend avalanche mode transition to FE being driven breakdown [21].…”
Section: Introductionmentioning
confidence: 58%
“…First exact solutions for the time dependent transport were obtained by using Monte Carlo (MC) simulations [19] and numerical solutions to the time dependent Boltzmann equation [20,21]. Numerous approximate experimental and theoretical papers have been published on the breakdown in RF using simplified semi-analytic forms [22][23][24][25][26]. At the same time fluid, hybrid and particle-in-cell (PIC) models of RF plasmas include early stages of the growth of ionization [18,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to appear small surface bulges, and cause local field amplification, so the electric field intensity below 10 8 V m −1 will also lead to field emission. 11,29) According to the breakdown voltage corresponding to the electrode gaps in Fig. 6.…”
Section: Analysis Of the Field Emissionmentioning
confidence: 99%